Mannogalactoglucan from mushrooms protects pancreatic islets via restoring UPR and promotes insulin secretion in T1DM mice - Ting Liu; Si Chen; Yunhe Qu; Lujuan Zheng; Xiaoxuan Yang; Shuhan Men; Yuanning Wang; Hanrui Ma; Yifa Zhou; Yuying Fan (Food Science and Human Wellness)
Type 1 diabetes mellitus (T1DM) lacks insulin secretion due to autoimmune deficiency of pancreatic β-cells. Protecting pancreatic islets and enhancing insulin secretion has been therapeutic approaches. Mannogalactoglucan is the main type of polysaccharide from natural mushroom, which has potential medicinal prospects. Nevertheless, the antidiabetic property of mannogalactoglucan in T1DM has not been fully elucidated. In this study, we obtained the neutral fraction of alkali-soluble Armillaria mellea polysaccharide (AAMP-N) with the structure of mannogalactoglucan from the fruiting body of A. mellea and investigated the potential therapeutic value of AAMP-N in T1DM. We demonstrated that AAMP-N lowered blood glucose and improved diabetes symptoms in T1DM mice. AAMP-N activated unfolded protein response (UPR) signaling pathway to maintain ER protein folding homeostasis and promote insulin secretion in vivo. Besides that, AAMP-N promoted insulin synthesis via upregulating the expression of transcription factors, increased Ca2+ signals to stimulate intracellular insulin secretory vesicle transport via activating calcium/calmodulin-dependent kinase II (CamkII) and cAMP/PKA signals, and enhanced insulin secretory vesicle fusion with the plasma membrane via vesicle-associated membrane protein 2 (VAMP2). Collectively, these studies demonstrated that the therapeutic potential of AAMP-N on pancreatic islets function, indicating that mannogalactoglucan could be natural nutraceutical used for the treatment of T1DM.